Bisnis Sekuritas Perspektif Ekonomi Islam - Aji Damanuri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze the securities business from an Islamic economic perspective, especially related to sharia principles in investment and securities trading activities. In Islamic economics, financial transactions must be free from the elements of usury, uncertainty, and luck. This study uses a qualitative method with a literature study approach, reviewing literature related to the capital market, DSN-MUI fatwas, and Islamic economic theory. The results showed that the securities business is acceptable in Islam as long as it complies with sharia principles, such as through sharia stocks, sukuk, and sharia mutual funds. However, there are still challenges in the implementation of sharia securities business, especially in ensuring transparency and sharia compliance in the capital market. This study emphasizes the importance of regulation and supervision to ensure that the securities business runs according to the principles of Islamic economics, so that it can become a halal and ethical investment instrument.